Experiments on creativity and work design. Issue 3 (5th March 2021) - Rodet, Cortney S.
Abstract: Creative jobs make up an increasingly large part of the economy. While contextual factors of work design have been shown to affect job performance in various settings, their impact on creative tasks is understudied. This study uses a controlled laboratory experiment to understand the impact of time constraints and goal setting on creativity. I find that reducing task constraints by making time constraints ambiguous increases the creativity of ideas without undermining their quantity, relative to the baseline. I also find that a nonbinding quantity‐oriented goal increases the quantity of ideas without reducing creative quality. Likewise, a nonbinding creativity‐oriented goal increases the creativity of ideas without decreasing the number of ideas. Results indicate that work design is an important factor when developing strategies for cultivating creativity, and managers have several tools at their disposal.